Zinc fertigation studies in Nagpur mandarin (Citrus reticulata) grown on black clay soil - SHIRGURE, P S; SRIVASTAVA, A K (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted for four seasons (2013–17) on 12-year-old bearing Nagpur mandarin (Citrus reticulata Blanco) plants budded on rough lemon rootstock (Citrus jambhiri Lush) at ICAR-Central Citrus Research Institute, Nagpur, Maharashtra. Six zinc-based treatments, viz. S100 as soil application of ZnSO4 (100 g/plant), S200 as soil application of ZnSO4 (200 g/plant), S300 as soil application of ZnSO4 (300 g/plant, F100 as fertigation of ZnSO4 (100 g/plant), F200 as fertigation of ZnSO4 (200 g/plant) and F300 as fertigation of ZnSO4 (300 g/plant) with uniform doses of macronutrients (450 g N + 150 g P2O5 + 150 K2O/tree/year) were evaluated in a randomized block design (RBD) with four replications on a smectite rich alkaline black clay soil. Significantly higher concentration of Zn in index leaves was observed with fertigation treatments than soil application treatments with regard to fruit yield and quality. The fruit yield was observed significantly lower with soil application of ZnSO4 (11.5–13.95 tonnes/ha with S100-S300) than fertigation treatments (15.6–16.4 tonnes/ha with F100-F300). The fruit quality parameters were observed much higher with F200 followed by F300. On the other hand, the lowest acidity (0.82%) and higher TSS to acidity ratio (11.52) were observed with F200. Hence, the treatment F200, split through 4 pulses at 40 days interval from anthesis to the fruit development stage proved highly efficient for quality production of Nagpur mandarin in central India.